أبعاد تمكين العاملين والولاء التنظيمي في قطاع الخدمات - نفيسي, الصالح; بوزيد, سليمة (جامعة الوادي - University of Eloued, 2021)
هدفت هذه الدراسة إلى تعريف تمكين العاملين والوقوف على علاقته بالولاء التنظيمي لدى موظفي وعمال مؤسستي الصحة العمومية بعين التوتة، وتكوّن مجتمع البحث من (588) موظفا وعاملا بكلا المؤسستين، وأختيرت عينة طبقية احتمالية بنسبة20% من مجتمع الدراسة أي 111 مبحوثا. واعتمدت رزنامة أس بى سس لتحليل ومناقشة الاستبانة. وتوصلت الدراسة إلى وجود علاقة إيجابية دالة احصائيا بين تمكين العاملين والولاء التنظيمي لدى موظفي وعمال مؤسستي الصحة بعين التوتة. وأوصت الدراسة باستغلال هذه العلاقة من أجل تقديم خدمات أفضل لتحقيق كل الأهداف المسطرة. Abstract: This study aimed at defining the empowerment of workers and finding its relationship with organizationa loyalty among employees and workers of the two public health institutions in Ain Touta, and the research community consisted of (588) employees and workers in both institutions, and a probable stratified sample was selected at 20% of the study population, i.e. 111 respondents. An SPSS calendar was adopted to analyze and discuss the questionnaire. The study concluded that there is a positive and statistically signifycant relationship between the empowerment of workers and organizational loyalty among employees and workers of the two health institutions, Ain Touta. The study recommended using this relationship in order to provide better services to achieve all the stated objectives.
دراسة ميدانية بمؤسستي الصحة العمومية بعين التوتة
مقال
Keywords: تمكين العاملين، الولاء التنظيمي، الخدمات، الصحة; Empowerment of employees, organizational loyalty, services, health